Proceedings of the 2011 Conference on Design &Amp; Architectures for Signal &Amp; Image Processing (DASIP) 2011
DOI: 10.1109/dasip.2011.6136896
|View full text |Cite
|
Sign up to set email alerts
|

High level design of adaptive distributed controller for partial dynamic reconfiguration in FPGA

Abstract: Controlling dynamic and partial reconfigurations becomes one of the most important key issues in modern embedded systems design. In fact, in such systems, the reconfiguration controller can significantly affect the system performances. Indeed, the controller has to handle efficiently three major tasks during runtime: observation (monitoring), taking reconfiguration decisions and notify decisions to the rest of the system in order to realize it. We present in this paper a novel high level approach permitting to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In this review we divided these applications into eleven categories and in each category we presented the applications with most documents related to them, totaling 150 applications described in this review. For digital control we found that the most important control techniques are implemented in FPGAs, like fuzzy control [1499][1500][1501][1502], PID [69,1503,1504], model predictive control [73,76,1505], adaptive control [80,81,1506], sensorless control [1507][1508][1509] and distributed control [96,99,101]. These digital control techniques were implemented in FPGAs due the high speed response that a hardware digital control FPGA-based implementation can achieve and its reconfiguration capability, allowing control application to high speed system such as induction motors [1507,[1510][1511][1512], torque control [75,1513,1514], Brushless DC (Direct Current) motors [1515][1516][1517], current control [1518,1519], among others [65,[1520][1521][1522][1523].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review we divided these applications into eleven categories and in each category we presented the applications with most documents related to them, totaling 150 applications described in this review. For digital control we found that the most important control techniques are implemented in FPGAs, like fuzzy control [1499][1500][1501][1502], PID [69,1503,1504], model predictive control [73,76,1505], adaptive control [80,81,1506], sensorless control [1507][1508][1509] and distributed control [96,99,101]. These digital control techniques were implemented in FPGAs due the high speed response that a hardware digital control FPGA-based implementation can achieve and its reconfiguration capability, allowing control application to high speed system such as induction motors [1507,[1510][1511][1512], torque control [75,1513,1514], Brushless DC (Direct Current) motors [1515][1516][1517], current control [1518,1519], among others [65,[1520][1521][1522][1523].…”
Section: Discussionmentioning
confidence: 99%
“…Each cell has autonomy in local optimization and also all integrate a large complex system [95]. FPGA-based distributed control techniques have been used for applications like micro-electromechanical systems arrays for air-flow planar micro-manipulation [96], music playing robots [97][98][99], telescopes control [100] and for reconfigurable FPGA-based systems [101][102][103].…”
Section: Digital Controlmentioning
confidence: 99%
“…They have also defined other extensions to support some Xilinx specific concepts such as bus macro, which permits routing between static and reconfigurable regions, the Internal Reconfiguration Access Port (ICAP), which assures the configuration memory read/write at run-time and the Reconfigurable Hardware Accelerator (RHA). Some control mechanisms have been added in (Cherif et al, 2011). A distributed modular reconfiguration controller has been presented.…”
Section: Reconfigurability Under Gaspard Frameworkmentioning
confidence: 99%